High-P-T experimental constraints on the genesis of post-collisional porphyry Cu-Au magmas: A case study from the southeastern Tibetan Plateau - Gong Liu; Xian-Wu Bi; Lei-Luo Xu; Wei Du; Lin-Bo Shang; Jing-Jing Zhu; Ming-Liang Huang; Rui Ma (Lithos, 2026)

Quality formation mechanism of shiitake mushrooms during multiphase microwave drying (MMD) - Zhenbin Liu; Jia Luo; Jiayi Zhang; Rui Weng; Wenchao Liu; Hongbo Li; Huan Cheng; Dong Wang; Hengchao E; Lu Tian; Haizhen Mo; Liangbin Hu (Food Control, 2026)

Knockout of kdm4aa inhibits early embryonic development in zebrafish via downregulating cyp26a1 - Rui Deng; Xinqing Cai; Hui Jiang; Yuting Luo; Weiran Chai; Bingshe Han; Junfang Zhang (Molecular Genetics and Genomics, 2026)

pH regulation of 1,2-bis(trimethoxysilyl)ethane hydrolysis pathways for enhanced wet state stability of TEMPO-oxidized cellulose nanofiber aerogels - Aojia Zhang; Rui Teng; Quan Zhang; Xue Liu; Biyao Sun; Chengcheng Suo; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Managing nitrate pollution in mixed land-use watersheds: source attribution and removal revealed by isotopes and 15N pairing - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Junlin Shu; Xin Luo; Rui Zhang; Ke Pan (Ecological Engineering, 2026)

A flexible and electrically insulative thermal interface material with ultrahigh liquid metal loading via high internal phase strategy - Rui Dong; Junjie Zhao; Xiang Gao; Yingwu Luo (Chemical Engineering Journal, 2026)

A low-molecular-weight glucan from Lycium barbarum reprograms tumor-associated macrophages involving the Dectin-1/NOX2 axis to suppress hepatoma - Yanping Cai; Yunliang Chen; Chunjing Li; Hongxu Chen; Yi Ji; Shaojie Zhang; Ying Zhu; Shuiling Cao; Rui Xu; Xueqian Xie; Qi Yi; Qing Wang; et al. (Carbohydrate Polymers, 2026)

Revealing spatiotemporal patterns of metro tidal ridership and their relationships with TOD features: A dual-sequence clustering and explainable machine learning approach - Rui An; Zhaomin Tong; Xiping Yang; Yaping Wang; Ying Jing; Yaolin Liu; Lin Luo; Jiayu Liu (Travel Behaviour and Society, 2026)

A procedure for geostatistical inversion incorporating a high-resolution initial hydraulic-conductivity field from travel time inversion - Huiyang Qiu; Ning Luo; Yong Huang; Chao Zhuang; Xiaolan Hou; Walter A. Illman; Rui Hu (Journal of Hydrology, 2026)

Multi-scale mechanistic elucidation of hydrogen generation in chemical looping gasification of lignite using carbide slag - Xujie Luo; Senlin Dong; Jie Yang; Binbin He; Dongyang Li; Liping Ma; Bing Huang; Liang Chen; Qihong Cen; Heping Zeng; Rui Nie; Lan Shao (Journal of Environmental Chemical Engineering, 2026)

A multiomics perspective on ecological toxicity, environmental behavior, and synthetic microbiome restoration of RDX in soil - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Yu Zhang; Xue-gang Luo (Journal of Environmental Chemical Engineering, 2026)

CTAB-assisted synthesis of HoY2Ox composite oxide catalyst with highly exposed specific (211) plane for cyclohexene epoxidation - Yingjie Wang; Fang Wang; Yuting Luo; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu (Journal of Environmental Chemical Engineering, 2026)

Oxidized Late Devonian arc intrusion in the Jiangda area, eastern Tibet: Implication for heterogeneous porphyry Cu-Au fertility of Paleo-Tethyan arc magmas - Rui Ma; Ming-Liang Huang; Lei-Luo Xu; Jing-Jing Zhu; Bao-Di Wang; Hong-Rui Zhang; Rui-Zhong Hu; Xing-Chun Zhang; Xian-Wu Bi (Journal of Asian Earth Sciences, 2026)

Mechanical response of layered heterogeneous hydrate-bearing sediments to depressurization - Hua Du; Huie Chen; Fansheng Kong; Qing Wang; Yonggui Luo; Xiang Gao; Jinzhong Zhu; Lanting Fu; Rui Fu (International Journal of Rock Mechanics and Mining Sciences, 2026)

Processing sequence alters gelation fate of high-concentration soy protein systems via transglutaminase-mediated crosslinking - Wenzhe Luo; Xueer Yu; Rui Zhang; Xiaokang Na; Ming Du; Chao Wu (Innovative Food Science & Emerging Technologies, 2026)

Estimation of ultimate bearing capacity for geosynthetic-reinforced sandy soil foundations by physics-informed deep learning model - Geye Li; Chungsik Yoo; Panpan Shen; Qingming Wang; Minmin Luo; Rui Zhang; Chao Xu (Geotextiles and Geomembranes, 2026)

Climate and soil shape Daqu wheat quality and seed microbiome via rhizosphere taxa and microbial assembly - Kangjie Yu; Shuanghui Wang; Hanrui Shi; Rui Luo; Zijian Chen; Yi Xia; Qingdong Zeng; Yi Ma; Dejun Han (Food Research International, 2026)

Temporal graph convolutional networks with morphological adjacency matrix: microclimate prediction for building energy modeling - Qi Li; Maomao Hu; Rui Ma; Jiayu Chen; Xiaowei Luo (Energy and Buildings, 2026)

Rainfall reshapes intra-urban activity patterns: Multi-level insights from human mobility in China - Nan Wang; Yunyan Du; Jiawei Yi; Wenna Tu; Sheng Huang; Peixian Luo; Xiaoyue Wang; Dingchen Hu; Rui Xu; Fuyuan Liang (Computers, Environment and Urban Systems, 2026)

Experimental investigation of the gas desorption–diffusion behavior of multi-scale outburst-prone coal under constant desorption pressures - Chaojun Fan; Rui Zhu; Lei Yang; Mingkun Luo; Xiang Fu; Xuan Liu; Xiaofeng Jiang (Chemical Engineering Journal, 2026)

Oxygen-vacancy-mediated BrO3− electroreduction: Positively charged microenvironment enables directional diffusion and spontaneous adsorption - Xiangbin Huang; Yue Cheng; Zhipeng Luo; Ruiqi Zheng; Yangying Zhao; Salman Farissi; Rui Liu; Gong Zhang; Xin Yu; Huabin Zeng (Chemical Engineering Journal, 2026)

Reaction kinetics of typical inorganic salts in H2–Air explosion suppression and the synergistic regulation mechanism of multi-elements - Qiuhong Wang; Rui Guo; Zhenmin Luo; Hu Wen; Xianfeng Chen; Wenzhe Mao; Qingfeng Wang; Qiulin Li; Yifan Li (Chemical Engineering Journal, 2026)

Flower-like PtCuTe nanozymes for synergistic photothermal and Fenton-like antibacterial therapy in infected wound healing - Ding Luo; Ji Cheng; Hao Zhang; Rui Liu; Hanjing Lu; Xudong Liu; Yuji Weng; Yunjun Zhang; Jianli Liu; Xiangyan Meng; Jinghua Li; Qi Lv; et al. (Chemical Engineering Journal, 2026)

Transparent, bio-based dielectric films with ultrahigh breakdown strength fabricated from hydrogen-bonded cellulose acetate and tannic acid for energy storage - Rui Luo; Xin-rui Xiao; Zhe-hao Kang; Chao-qun Wu; Ting Huang; Nan Zhang; Yong Wang (Carbohydrate Polymers, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Regulatory mechanisms underlying dynamic variation of DHA, EPA, and odd-chain fatty acids content in Auran tiochytrium sp. SZ13 - Rui Luo; Buwen Sun; Jiaxing Li; Nannan Zhang; Meihan Chen; Ziyu Du; Shuo Li; Jialin Guo; Bin Liu; Dongzhe Sun (Algal Research, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

A pH-responsive sequential-releasing hydrogel breaks the infection-inflammation-oxidative stress cycle to promote vascularized healing in refractory anal fistula - Qiuqun Xiao; Kailan Liu; Manzhen Zhou; Ruyi Peng; Luyang Dai; Rui Zhang; Lin Luo; Yong Xue; Yunrui Hu (Chemical Engineering Journal, 2026)

Binocular-depth-guided dual-view camera-LiDAR fusion for kiwifruit pose estimation in robotic harvesting - Shiao Niu; Leilei He; Qilin Gong; Qichen Huang; Ruichao Luo; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Anastasia Grecheneva; et al. (Computers and Electronics in Agriculture, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Nanoconfinement-enhanced peroxymonosulfate activation by Co single atoms in hollow mesoporous carbon: Roles of active-site chemistry and mesoscale confinement - Hao Luo; Junli Zheng; Jiaxin Liu; Junjun Ma; Rui He; Chuqi Huang; Rong Xie; Qintie Lin (Water Research, 2026)

The influence of exogenous amino acids on nitrogen cycling in the rhizosphere soil of maize and nitrogen absorption by the roots - Xinyi Luo; Youhao Liu; Zefei Wang; Rui Wang; Yaqi Wang (Rhizosphere, 2026)

Research on the intelligent obstacle avoidance and path optimization approaches for ship navigation in ice regions - Zhichen Liu; Sihui Wu; Mingyuan Jiang; Ying Li; Rui Gao; Jianan Luo (Ocean Engineering, 2026)

The differential interfacial regulation of dolomite and apatite utilizing a novel modified macromolecule depressant for efficient upgrading of phosphate ores - Yang Xu; Rui Ma; Bingqiao Yang; Zhenyu Zhang; Yudi Yan; Huihua Luo; Weijun Peng (Minerals Engineering, 2026)

Ecotoxicological impacts of TNT and its key transformation intermediates in freshwater microcosms and their effective remediation by a bicarbonate-activated peroxide system - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo; Yong-bing Zhu; San-ping Zhao (Journal of Water Process Engineering, 2026)

A synthetic microbiome drives a multi-omics response to remediate 1,4-dithiane–contaminated soil and simultaneously suppresses antibiotic resistance genes - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Journal of Hazardous Materials, 2026)

Highly efficient and selective recovery of rare earths from NdFeB waste via water-regulated deep eutectic solvent - Jianru Li; Cunying Xu; Rui Luo; Qibo Zhang; Yixin Hua; Mingyuan Gao; Rongrong Deng; Mengwei Guo; Yan Li (Journal of Cleaner Production, 2026)

Microwave-assisted synthesis of FeN Co-doped ZIF-8 derived carbon for low-concentration lithium recovery via CDI: Adsorption performance and mechanism - Yongsi Xie; Jiemei Fu; Chunxue Li; Juan Luo; Rui Ma; Shichang Sun (Desalination, 2026)

Environment-responsive multi-enzymed Cu/Cu2O@NC nanorhombic nanoplatform for infected wound antimicrobial treatment - Ji Cheng; Hao Zhang; Yueting Jiang; Zuojia guo; Rui Liu; Xiantao Lin; Hanjin Lu; Yunjun zhang; Wenxuan Fan; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Zr/Al surface enrichment boosts structural stability and electrochemical properties of ultra-high nickel cathode materials - Liang Luo; Jie Chen; Zhongyuan Luo; Rui Zhou; Yuanyuan Chen; Xinyu Zhao; Xianshu Wang; Shunyi Yang; Yingjie Zhang; Yannan Zhang; Kaomin Zhang; Peng Dong; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota” [Carbohydrate Polymers 339 (2024) 122255] - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2026)

Study on thermal damage and pore structure evolution of granite under high temperature and different cooling methods - Yingjie Zhang; Chuanqu Zhu; Yanlin Zhao; Lianyang Zhang; Shuailong Lian; Rui Luo; Pei Tang (Bulletin of Engineering Geology and the Environment, 2026)

Role of immune dysregulation in aristolochic acid–induced multisystem toxicities: an insight from systems toxicology - Jing Yang; Xiaodan Lai; Hongwei Luo; Yue Luo; Bin Chen; Jing Lei; Yuanqiang Wang; Yuanlin Ma; Rui Xiong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Microcrack-Driven Degradation in Rock Compaction Deformation and Damage Under Different Environmental Effects - Huiguan Chen; Cheng Zhao; Rui Zhang; Xiangcheng Que; Biaohe Zhou; Haoyu Pan; Yinfeng Luo (Rock Mechanics and Rock Engineering, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Effects of Alhagi sparsifolia root content and soil moisture content on soil deformation and strength under different freeze-thaw temperature conditions - Meixue Zhang; Qinglin Li; Xuanbing Luo; Wenjuan Chen; Rui Wang; Shuailong Yu; Guang Yang (Soil and Tillage Research, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

PRISM: Turning prediction uncertainty into cost-effective management decisions for cadmium-contaminated rice - Ziqian Zhong; Qihong Zhu; Xinliang Liu; Shufang Pan; Lei Luo; Xin Luo; Hanhua Zhu; Rui Liu; Lin Zou; Daoyou Huang (Journal of Hazardous Materials, 2026)

Enhancing microseismic P-wave arrival detection: An FCM-AIC approach with an application to underground mines - Sicheng Wang; Yongjiang Luo; Xing Wang; Xueyi Shang; Rui Tao (Journal of Applied Geophysics, 2026)

Tuning the Cu/Zn ratio in copper-zinc phosphate catalysts: Mechanistic insights into activity and stability of anisole acetylation - Yuting Luo; Yingjie Wang; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu; Fang Wang (Fuel, 2026)

Post-combined prestressed continuous composite bridge deck for mitigating concrete cracking: Experiment, numerical simulation, and theoretical analysis - Qingtian Su; Rui Zhao; Zhanchong Shi; Disheng Zou; Lefei Huang; Feiran Li; Hui Luo (Engineering Structures, 2026)

The acute toxicity of Daphnia magna to mixtures of herbicides (glyphosate, glufosinate-ammonium) and heavy metals (Cu, Cd) are concentration-dependent - Rui Yang; Yingpeng Yu; Wei Wei; Xiaoli Xu; Xinjun Yu; Mingzhong Luo (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A Process-based classification of meteorological mechanisms influencing airborne pollen concentrations in northern and northwestern China - Zining Yuan; Huiyu Ning; Xingqin An; Qingyu Wei; Defang Wei; Wenqiao Xue; Ning He; Lina Di; Xinli Yang; Ying Li; Rui Li; Hongjian Li; et al. (Atmospheric Research, 2026)

A multi-tier methodology for Scope 3 emissions accounting in complex supply chains: mathematical framework and empirical insights from China - Rui Luo; Qingge Geng; Chuan Shi; Chuangyin Dang (Journal of Industrial Ecology, 2026)
Scope 3 emissions—indirect greenhouse gas emissions across a company’s value chain—often constitute the largest share of corporate carbon footprints yet remain inadequately measured due to methodological challenges. Unlike the GHG Protocol’s general guidelines, which leave multi-tier allocation, circular dependencies, and complex ownership to individual practitioners, this paper develops an integrated, algorithmically implementable framework for multi-tier Scope 3 emission calculation. Our three-component methodology comprises: a tier-specific economic allocation model using revenue–transaction ratios, a path-based circular dependency resolution algorithm, and an equity-weighted attribution mechanism for complex ownership structures. Unlike sector-level approaches such as Economic Input–Output Analysis (EIOA) and Multi-Regional Input–Output (MRIO) models, our framework operates at the firm-transaction level, enabling company-specific accountability. We empirically validate this framework using data from Chinese companies across nine industries, tracing carbon flows through supply chains up to five tiers deep. Tier 1 suppliers account for a median of 99.6% (bootstrap 95% CI [98.5%, 99.8%]; mean: 89.4%) of total calculated emissions (mean 37,305.1 tCO 2 ), confirmed by Friedman test ( $$χ ^2 = 285.40$$ χ 2 = 285.40 , $$p = 1.52 × 10^{-60}$$ p = 1.52 × 10 - 60 ) and pairwise Wilcoxon signed-rank tests (all $$p_{BH} < 0.001$$ p BH < 0.001 ). Comparison with company-reported Scope 3 reveals industry-specific discrepancies, with calculated-to-reported ratios ranging from near-zero (Real Estate) to 3.157 (Industrials), indicating significant heterogeneity and potential under-reporting. We identify dominant intra-industry carbon flows within Industrials (2,099,959.4 tCO 2 ) and significant cross-sector transfers from Materials to Financials (91,183.8 tCO 2 ). Network analysis reveals that 32.5% of supply chain nodes participate in circular dependencies, with the largest strongly connected component containing 947 nodes; our resolution algorithm eliminates double counting while preserving mathematical consistency. These findings support focusing carbon reduction efforts on Tier 1 and Tier 2 suppliers and carry direct implications for China’s dual carbon goals through mandatory supply chain carbon disclosure frameworks and industry-specific reduction targets.

Calculation of hydrogeological parameters based on a high-flow long-duration water release test of multiple deep boreholes, Xiadian coalfield, North China - Fang Li; Rui Luo; Zhijia Yu; Wubin Gao; Jianggen He; Yu Ping; Shiyuan Tian; Zihan Wang; Tao Cheng; Colin G. Farquharson; Xinyi Wang (Hydrogeology Journal, 2026)

Form-associated quality variation and exploratory transcriptome-metabolome characteristics in selected Gastrodia elata tuber samples - Rui Yang; Fu-Lai Luo; Ping Wen (Plant Biotechnology Reports, 2026)

Palaeoenvironmental evolution and organic matter enrichment in the Early Silurian Yangtze Foreland Basin: Tectonosequence stratigraphic insights for shale gas exploration - Xinguo Li; Rui Liu; Yuxuan Wang; Junwei Pu; Hui Liu; Lu Xu; Tongtong Luo; Xiucheng Tan; Weiming Chen; Ruiying Chao (Applied Geochemistry, 2026)

Dendrobium officinale leaf extract extends the mean lifespan in Caenorhabditis elegans via the DAF-16/SOD-3 axis - Cheng Gong; Shu Feng; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Shikuan Zhao; Rui Zhou; Li Feng; Yunfei Ge; Ruijuan Yang; Chongye Fang; Xiaocui Du (Biogerontology, 2026)

Unveiling the participation of microbiomes in the trait formation of economically important Pyropia haitanensis varieties - Yi Liu; Jingyi Wang; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Huifeng Cai; Haimin Chen (Aquaculture, 2026)

SGDC-UIE: A Semantic Guidance Network with Degradation Consistency for Underwater Image Enhancement - Rui Ming; Jianshan Zhang; Taotao Lai; Haibo Luo; Jiancheng Yang (Journal of Marine Science and Engineering, 2026)
Underwater images often suffer from color distortion, low contrast, and structural blurring caused by wavelength-dependent absorption and scattering, which degrade both visual observation and downstream perception. Existing underwater image enhancement methods usually learn image-level restoration mappings, while the relationships among semantic regions, degradation patterns, and restoration responses are not fully exploited. In this paper, we propose a Semantic Guidance Network with Degradation Consistency for Underwater Image Enhancement (SGDC-UIE). Specifically, SGDC-UIE first extracts dense semantic responses from a frozen DINOv3 prior and converts them into foreground, boundary, and background region gates. These gates are then used to guide pseudo-physical degradation estimation, producing attenuation-like, transmission-like, illumination, structure, and background-light priors for region-aware restoration. These pseudo-physical priors are learned, bounded conditioning variables rather than calibrated estimates of underwater optical parameters. Based on these degradation conditions, a dual-branch restoration network corrects low-frequency color and illumination degradation while recovering high-frequency structural details through semantic-aware wavelet restoration. The color-restored and structure-restored outputs are further integrated by a degradation-consistent fusion gate, which adaptively balances visual fidelity and task-relevant structure preservation. In addition, grouped supervision with quality-anchor replay stabilizes task-aware fine-tuning and reduces visual-quality drift. Extensive experiments on paired and no-reference underwater enhancement benchmarks, semantic segmentation, and underwater object detection show that SGDC-UIE achieves competitive restoration quality and improves the usability of enhanced images for downstream perception.

Triaxial Creep Behavior and Meso-structural Characteristics of Rock-Concrete Composites with Different Interface Roughness - Weijing Yao; Hanbing Xu; Shengqi Yang; Yongjiang Luo; Shaoge Rui; Jianyong Pang (Rock Mechanics and Rock Engineering, 2026)

A voyage-level threshold analysis of planned turnaround vulnerability in cruise ports from an AIS big data perspective - Shengjun Gan; Shikai Hu; Han Zhang; Kai Luo; Rui Yang; Salvatore Antonio Biancardo (Frontiers in Marine Science, 2026)
Introduction Cruise port operations are facing increasingly significant challenges in departure reliability amid frequent climate variability, port congestion, supply chain disruptions, and geopolitical risks. Unlike existing studies that mainly explain cruise delays from the perspectives of weather conditions, external shocks, or supply chain risks, this paper focuses on whether port turnaround planning itself may constitute an endogenous source of vulnerability. Methods To identify this issue, this study uses the daily AIS data for the United States released by Marine Cadastre. These data are combined with planned berthing information, weather data, and vessel characteristics to construct a sample of 3,238 cruise ship–port–day observations. The study defines planned turnaround time as a time-based buffer resource in voyage-level operations. It then applies a fixed effects model, a threshold regression model, a half-hour interval model, mechanism tests, heterogeneity analysis, and moderation analysis to systematically examine the impact of planned turnaround time on departure reliability and its operational boundaries. Results The results show a significant threshold-type nonlinear relationship between planned turnaround time and departure delay. An 8.5-hour threshold is identified as the main data-driven cutoff, while a meaningful buffering effect is mainly observed within 8 hours. The interval of 8.0–8.5 hours is better viewed as a transition range where marginal benefits begin to decline. Mechanism tests indicate that actual berthing service time is the most stable primary transmission channel of planned turnaround vulnerability, while port queuing pressure and berth occupancy pressure further modify the marginal effect of planned turnaround time. Discussion This study moves the analysis of cruise departure delays from explanations based on exogenous shocks to the identification of endogenous vulnerability. By revealing that planned turnaround time itself can become a source of risk under specific threshold conditions, these findings complement existing resilience literature that has primarily focused on external drivers. It provides new micro-level evidence for understanding the resilience of cruise port operations, optimizing schedule planning, and improving port coordination efficiency.

An Integrated GPU‑Accelerated Framework for Closed‑Loop Generation of 3D Morphology–Meso‑mechanics Coupled Random Fields of Rock Particles - Jianqing Jiang; Junjie Zheng; Jin Chang; Shilin Luo; Rui Zhang; Shi Zuo (Rock Mechanics and Rock Engineering, 2026)

A Variogram Model Based on Spatial Decay of Gravity Anomaly Covariance - Xiao-yu Xie; Kai-xin Luo; Ju-liang Cao; Shao-kun Cai; Rui-hang Yu; Qi-qin Hu; Yan Guo; Bai-nan Yang (Applied Geophysics, 2026)

Unraveling the effects of the built environment on ride-shareability: Evidence from Shanghai - Longxu Yan; Junnan Chen; Zixin Luo; Mi Diao; Zhejing Cao; Rui Zhu; Yang Hu (Travel Behaviour and Society, 2026)

3D analytical modeling of seismic ground motion and energy partitioning in the marine site subjected to obliquely P-SV waves - Guang-rui Feng; Li-quan Xie; Chen-wei Luo (Soil Dynamics and Earthquake Engineering, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Synergistic modification of perilla protein isolate by high-speed dispersion-assisted microfluidization and phosphorylation: Effects on structural and functional properties - An Luo; Qiaoli Zhao; Zhuo Wang; Rui Li; Qin Liu; Saiyi Zhong (Innovative Food Science & Emerging Technologies, 2026)

Integrative multi-omics combined with molecular docking and molecular dynamics simulations elucidates the mechanism driving the transition from green notes to fruity aroma during musang king durian ripening - Zhongyan Li; Tianci Yan; Bin Xu; Xulu Luo; Yumei Ding; Wei Fan; Qin Qiao; Shaojie Yuan; Hui Guo; Meng Zhang; Yan Zhao; Rui Wang; et al. (Food Research International, 2026)

Transcriptomic and metabolomic insights into the combined toxicity of acute glyphosate and copper exposure in water flea (Daphnia magna) - Xiaoli Xu; Rui Yang; Mingzhong Luo; Qiuhong Zhong; Xiaofu Wang; Yanhui Duan; Junfeng Xu; Wei Wei (Environmental Research, 2026)

Economic rhythms and green tides: Charting China's dual dividends through synergistic policies - Yu-Jie Hu; Rui Zhang; Ailing Luo; Yu Hao (Environmental Impact Assessment Review, 2026)

Engineered MBene-integrated anisotropic aerogel with synergistic hydrogen-bond network and superior photothermal conversion for efficient solar-driven desalination and purification - Xinyi Wang; Rongtao Zheng; Cuilian Wen; Lijin Luo; Jiansen Wen; Haonan Zhao; Rui Xiong; Frank Marken; Yin Yuan; Baisheng Sa (Desalination, 2026)

Upgrading H2/CO2-containing waste gas to single cell protein: Tolerance and response of Cupriavidus necator H16 to hydrogen sulfide - Jie Wang; Rui Li; Manqian Wang; Xuening Wang; Min Xue; Ankun Xu; Kai Luo; Xiaolei Fan; Rongbo Guo; Shanfei Fu (Chemical Engineering Journal, 2026)

Enzymatically synthesized native-like guaiacyl dehydrogenation polymer as a formaldehyde-free adhesive for high-strength, water-resistant plywood - Rui Luo; Wenhao Liu; Qian Tu; Yuanpu Wang; Junjun Chen; Junxian Xie; Rong Zhang; Nianjie Feng; Peng Wang (Chemical Engineering Journal, 2026)

High transparent, high strength and high energy storage capability of cellulose triacetate films via incorporating cellulose nanocrystal - Xin-rui Xiao; Rui Luo; Jing-hui Yang; Nan Zhang; Yong Wang (Carbohydrate Polymers, 2026)

A Lepidoptera Synthesis Phylogeny of 11,001 Species and Its Application in Phylogenetic Profiling of Herbivore DNA Barcodes: Towards an Integrative Phylogenetic Framework for Insects - Douglas Chesters; Ming‐Qiang Wang; Perttu Anttonen; Jing‐Ting Chen; Rui Cheng; Yi Li; Arong Luo; Michael C. Orr; Tingting Xie; Qingsong Zhou; Chao‐Dong Zhu (Zoologica Scripta, 2026)
We herein constructed a phylogeny of Lepidoptera synthesizing multiple information types, a phylogenomics backbone, a multigene supermatrix with species‐comprehensive DNA barcodes, and topological information from a compiled database of standardized machine‐readable trees from over 100 previous studies. We then applied the new phylogenetic synthesis as a profiling framework for a large DNA barcode dataset of caterpillars from a tree diversity experiment. The synthesis phylogeny comprised 11,001 species. Phylogenetic information content was taxonomically skewed towards butterflies (i.e., Nymphalidae, Papilionidae and Pieridae), and parts of Macroheterocera (Geometridae, Sphingidae, Saturniidae and Bombycidae), while undersampling of Lepidoptera species diversity was present in Erebidae, Noctuidae, Gelechioidea and Pyraloidea. Caterpillar Phylogenetic Diversity (PD) increased with tree richness in the diversity experiment regardless of processing choices in calculating caterpillar PD, including whether calculated on plot OTU alone, plot OTU placed onto a simple reference phylogeny or plot OTU placed to the comprehensive reference phylogeny. Stronger correlations between tree diversity and uncorrected Faith's PD of caterpillars were observed where OTU were placed onto the full reference tree, and where long branch OTU were removed prior to PD calculation, though no significant differences in the strength of the tree diversity effect across context and processing choice were observed for standardized PD. In calculation of plot‐level PD, focus should remain on community sample size, with the results herein supporting the use of any available reference phylogeny as context, though correspondence of PD indices to environmental gradients might be stronger where plot OTU can be placed to a comprehensive reference phylogeny. The phylogeny presented herein enables inference of varied evolutionary information for Lepidoptera DNA barcode sets.

Synergistic catalytic co-liquefaction of lignin and polyethylene in a water–pentane biphasic system: An efficient route to sustainable liquid fuels - Shitong Yu; Zhitong Ge; Samudrala Shanthi Priya; Kuen Kee Hyun; Saidakmalov Saidalo; Khusenov Arslonnazar; Samir I. Gadow; Jun Xiao; Rui Xiao; Zhicheng Luo (Waste Management, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Estimating multi-scale ventilation corridors in complex 3D urban space: A graph-based least-cost path model - Yifan Luo; Xinyu Yu; Majid Nazeer; Man Sing Wong; Jinxin Yang; Rui Zhu (Urban Climate, 2026)

An adaptive spatiotemporal coupling approach for dynamic collision risk perception and quantification in intelligent vessels - Zhichen Liu; Mingyuan Jiang; Ying Li; Rui Gao; Yu Du; Jianan Luo (Ocean Engineering, 2026)

Ascosphaera apis-derived microRNA-like RNAs mediate cross-kingdom regulation of gene expression in western honeybee larvae - Xiaoxue Fan; Nian Fan; Tao Wu; Jing Kang; Jiarun Yang; Jing Tian; Xihan Luo; Dafu Chen; Jianfeng Qiu; Rui Guo (Journal of Invertebrate Pathology, 2026)

Defect-engineered nitrogen-doped carbon from tannic acid for highly efficient peroxydisulfate activation via nonradical pathways - Rui Luo; Tong Yu; Kexin Tai; Xiaoju Wen; Zongtang Liu; Binbin Qian; Qihui Xu; Haijiao Xie; Xiankun Wu (Journal of Environmental Chemical Engineering, 2026)

Effects of MFC-mediated iron tailings on heavy metals transformation and microbial communities during the aerobic composting of pig manure - Keping Li; Rui Yu; Xia Wu; Wencong Yang; Wenyue Shao; Yong Yu; Nana Luo; Jia Zhou (International Biodeterioration & Biodegradation, 2026)

Influence of Pt-Cu synergistic action and TiO2 core–shell structure on NH3-SCO and anti-aging performance - Zhenhua Ji; Zhongqiang Bao; Zihao Wu; Peng Zhang; Rui Yang; Ding Luo; Hao Chen (Fuel, 2026)

Divergent mechanisms of zinc and manganese in controlling cadmium transfer to rice grain: from big data to field verification - Rui Liu; Shufang Pan; Xinliang Liu; Lei Luo; Ziqian Zhong; Qihong Zhu; Hanhua Zhu; Xionghui Ji; Daoyou Huang (Environmental Pollution, 2026)

Wind-driven Kelvin waves induce quasibiweekly oscillations in the coastal water of south Maritime Continent - Zhengpu Luo; Dwiyoga Nugroho; Adi Purwandana; Dezhou Yang; Zheng Wang; Rui Li; Xu Wang; Yuxuan Li; Priyadi Dwi Santoso; Muhammad Fadli; Bayu Priyono; Teguh Agustiadi; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Electrochemical induction of high performance electricity generation by novel marine electroactive Rossellomorea aquimaris MT01 - Dan Luo; Ke Xu; Rui Zhai; Xiaoyun Zheng; Jianyu He; Wu Qu; Wenyuan Huang; Jianxin Wang (Bioresource Technology, 2026)

Metabolic inflexibility across heart failure phenotypes: mechanisms and type-specific therapeutic implications - Li Chen; Xin-Rui Yang; Yan Jiang; Shi-Qi Cheng; Zhen-Xun Wan; Jin-Wen Wu; Ming-Tai Chen; Yuan-Yuan Li; Gang Luo; Meng-Nan Liu (Apoptosis, 2026)

From Crystal Structure to Dissolution Enhancement: Cocrystal Engineering of Resmetirom to Address Its Solubility Challenge - Chen Yang; Rui Zhu; Feipeng Zhang; Liang Hu; Xueyan Zhu; Xiangkui Liu; Ying Luo (Pharmaceutical Research, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Dynamic error elimination method of strapdown gravimeter based on artificial neural network - Shao-kun Cai; Yang Yu; Rui-hang Yu; Zhi-ming Xiong; Ju-liang Cao; Yan Guo; Bai-nan Yang; Kai-xin Luo; Mei-ping Wu (Applied Geophysics, 2026)

CTF-TL: Coarse-to-Fine temporal localization framework for precise recognition of posture transition behaviors in periparturient sows - Zikang Chen; Yan Luo; Chao Yuan; Kai Yan; Rui Diao; Jiachao Zhang; Mingxia Shen; Xiangbo Shu; Xingjian Gu; Mingzhou Lu (Computers and Electronics in Agriculture, 2026)

Valorization of industrial carbide slag via microwave processing: A low-cost route to high-performance CaO-based CO2 sorbents - Fang Wang; Yi Dong; Shaojun Luo; Zixia Tian; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Futing Xia; Jiayu Feng; Lijuan Jia (Journal of Environmental Management, 2026)

Biomass-derived modifiers customize polymeric nanofiltration membranes for enhanced lithium/magnesium ion selectivity - Xin-Xi Ding; Cheng Jiang; Jia-Wang Wang; Zi-Hui Wu; Rui Luo; Yue Zhao; Yue Wang; Dan-Dan Shao (Desalination, 2026)

Regulating proton migration by trace additive for ultra-stable Zn anodes - Yaowen Xu; Zhao Chen; Shaofei Wu; Rui Zhao; Qiao Luo; Xuanyuan Liao; Yaqin Wu; Yiman Xie; Wei Zhang; Liangjun Zhou; Weifeng Wei (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Dominant drivers of soil multifunctionality change: interactions among soil, plants, and the atmosphere - Tiantian Luo; Weiyi Zhou; Yun Shi; Fenghong Zhang; Guo Rui; Hongyuan He; Tao Wu; Hongxia Li; Yiting Ma (Plant and Soil, 2026)

Icaritin ameliorates MPTP-induced Parkinson's disease model by targeting the NLRP3 inflammasome pathway - Chengnian Yang; Yuanyuan Li; Tingting Liu; Rui Liang; Juan Huang; Yong Luo; Nanqu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Molecular Basis of Biostimulant-enhanced Recovery from Late-spring Frost in Vitis Vinifera: A Transcriptomic Dissection - Chaoyue Feng; Xi Chen; Xinyi Luo; Huiyu Zhu; Huiling Ma; Xiaojun Liu; Yulong Li; Quan Sun; Rui Wang; Yaqi Wang (Journal of Plant Growth Regulation, 2026)

Proteome profile analysis reveals regulatory mechanisms in the liver of Carassius auratus under short‐term salinity stress (10‰, 48 h) - Rui Zhao; Muhan Meng; Xiaolian Liu; Shuang Hao; Xin Luo; Ning Wu; Lin Ma; Sun Hongqing; Hongzheng You (Journal of Fish Biology, 2026)
Carassius auratus , a commercially important species in the ornamental aquarium industry, is sensitive to salinity fluctuations. In this study, 30 C. auratus of length 13.1 ± 2.9 cm and weight 103.8 ± 40.8 g/fish were placed into six plastic tanks (80 L) with five fish per tank. About 15 fish were exposed to 10‰ salinity for 48 h, while another 15 fish were kept in freshwater and continuously aerated (0‰) as a control. To investigate the effects of short‐term salinity stress (10‰, 48 h), proteomic profiling of the liver was conducted. Short‐term salinity stress resulted in 104 upregulated and 95 downregulated proteins in the liver of C. auratus . Gene ontology enrichment analysis indicated significant enrichment in areas such as proteolysis, nitrogen compound transport, cellular component, peptidase activity, acting on L‐amino acid peptides, endopeptidase activity, serine‐type peptidase activity and enzyme inhibitor activity. Furthermore, the Kyoto Encyclopedia of Genes and Genomes enrichment analysis identified mitogen‐activated protein kinase kinase kinase 7 (MAP3K7) as an essential regulated protein in the IL‐17 signalling pathway and glutamine synthetase (GS) in the arginine biosynthesis pathway. These findings suggest that short‐term salinity stress induces significant proteomic changes in C. auratus , with functional enrichment in peptide metabolism and enzyme regulation. Notably, MAP3K7 and GS may play crucial roles in coping with short‐term salinity stress, providing new insights into the proteomic regulatory mechanisms of C. auratus under short‐term salinity stress.

Quantification of 3D Fracture Network Characterization and the Coupling Mechanisms in Non-blasting SC-CO2 Fracturing: A Bayesian Calibrated Multiscale Complex Fracture Index - Chao Zhu; Jie Chen; Zhonghao Luo; Kunyong Guo; Wenhao Shi; Yuanyuan Pu; Yichao Rui; Deping Guo (Rock Mechanics and Rock Engineering, 2026)

Unveiling the “Glycolysis-Lactate-Lactylation” Axis: A Novel Target in Ischemic Cerebrovascular Disease - Yi Xie; Mengmeng Dai; Rui Liu; Ying Li; Hao Yan; Jiacheng Li; Xuantong Liu; Zhiyuan Yu; Shabei Xu; Wei Wang; Xiang Luo (Neuroscience Bulletin, 2026)
Ischemic cerebrovascular disease involves complex interactions between metabolic reprogramming and epigenetic regulation. Recent studies indicate that enhanced glycolysis and lactate accumulation under hypoxic conditions not only maintain cell viability by supplying energy but also participate in disease regulation through lactylation. Lactylation regulates gene expression, immune polarization, metabolic enzyme activity, and angiogenesis through epigenetic remodeling. In ischemic cerebrovascular disease, lactylation exerts dual roles: on one hand, it can induce neuronal death, exacerbate neuroinflammation, and form a vicious metabolic cycle; on the other hand, it can influence immune cell function and gene expression, thereby exerting neuroprotective effects. Accordingly, targeting lactate metabolism or lactylation-modifying enzymes holds considerable therapeutic potential. Nevertheless, the spatiotemporal regulation, synergistic effects, and broader physiopathological implications of lactylation warrant further in-depth investigation. This review systematically summarizes the role of the “glycolysis-lactate-lactylation” axis in the pathogenesis of ischemic cerebrovascular disease, and discusses its potential as a therapeutic target.

Antimicrobial polyketides from an endophytic fungus Arcopilus aureus HJ-7 from Ardisia mamillata Hance - Li-Qi Liang; Xian-Hua He; Chun-Yan Wei; Jing-Xian Zhao; Qian Wu; Min Liang; Jun Li; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2026)

Ultra-highly specific and visual detection of Vibrio pathogens in Porphyra using RPA-coupled CRISPR-LbaCas12a-LFD system - Xu-Xu Luo; Hai-Long Huang; Qi-Qin Liu; Hoi-Yan Kwok; Hai-Tao Ma; Hai-Bo Jiang; Rui Yang (Aquaculture, 2026)

YOLO-FR: An enhanced object detector for small object detection in complex scenes - Rui Fan; Renhao Jiao; Weigui Nan; Jin Dang; Zhixue Wang; Xuefeng Ge; Baiying Dong; Xiaoli Luo (Remote Sensing Applications: Society and Environment, 2026)

High-value utilization of chromium ore processing residue (COPR) through corn straw-soda roasting followed leaching processes - Cheng Tian; Zilong Li; Cunfang Lu; Rui Xu; Min Zhang; Lin Yang; Wenlin Xie; Zhengnan Zhong; Yuanyuan He; Juan Wen; Dan Luo (Journal of Environmental Chemical Engineering, 2026)

Low-alkali activated Ca2+-KNBC/SA aerogel from waste citrus peel: Efficient and selective removal of Cu(II) and Cd(II) in acidic wastewater - Jiajia Yang; Rui Zhang; Ying Lei; Jian Yang; Maiming Ye; Zhengyu Luo; Hailing Li; Xiaofeng Zhou; Yi Huang; Xinyu Wang; Peng He (Journal of Environmental Management, 2026)

Critical thresholds in urbanization-vegetation dynamics: Multiscale remote sensing evidence from Chinese cities - Yining Shen; Nan Wang; Yunyan Du; Jiawei Yi; Sheng Huang; Wenna Tu; Peixian Luo; Rui Xu; Dingchen Hu (Journal of Environmental Management, 2026)

Fabrication of dysphagia-friendly emulsion gels using tilapia protein: Synergistic effects of high-density ultrasonic modification and flaxseed gum interfacial complexation - Qiaoli Zhao; Hairong Deng; An Luo; Xinghao Tu; Jiaxi Ma; Rui Li; Zhuo Wang; Hongwei Wang; Saiyi Zhong (Food Chemistry, 2026)

A novel friction self-centering damper using nitrogen gas springs: Development, experiments, and seismic response control - Chengyu Bai; Jianyang Xue; Zheng Luo; Rui Liu; Sha Ding (Engineering Structures, 2026)

Abandonment duration shapes reuse strategies and benefits of abandoned cropland in China - Yixin Liao; Chenrui Luo; Xue Wang; Jialin Liu; Xiaoqi Huang; Xinliang Xu; Rui Qin; Yuanwei Qin; Luo Liu (Environmental Impact Assessment Review, 2026)

Surface charge and pore size regulation for nanofiltration membrane enables enhanced Co/Li separation performance - Rui Gao; Hui Shi; Zhiwei Qiu; Ruobin Dai; Xubiao Luo; Zhiwei Wang (Desalination, 2026)

A synergistic strategy to overcome temperature and concentration polarization in a joule-heating CNT/PTFE membrane distillation: From membrane preparation to process mathematic simulation - Tiantian Xu; Longji Li; Xiaojia Li; Liang Feng; Siyu Chen; Yang Xu; Yan Li; Zhiqing Luo; Zhirui Chen; Hongyi Li; Rui Wang; Feiyun Sun (Desalination, 2026)

A LiF-rich and Ag-embedded dual-artificial solid-electrolyte interphase for stable Li metal anodes - Xun-Lu Li; Jian Bao; Wenyu Zhao; Chong-Yu Du; Rui-Jie Luo; Cui Ma; Jie Zeng; Xuan Xu; Zhe Qian; Zhe Mei; Xinyang Yue; Yong-Ning Zhou (Chemical Engineering Journal, 2026)

Accelerating Sugarcane Breeding with Machine Learning: A Concurrent Multi-trait Predictive Approach - Haichuan Fan; Jing Chao; Xiaoyan Liu; Pengcheng Ma; Guanghu Zhu; Ming Li; Rui Yan; Xinyi Li; Yan Jing; Fengbing Li; Ting Luo; Prakash Lakshmanan (Sugar Tech, 2026)
A large and highly polyploid genome, long breeding cycles, low narrow-sense heritability of yield and its components, and persisting yield stagnation continue to challenge sugarcane variety improvement through both conventional and molecular breedings. To address this, this study developed an efficient phenotype-based concurrent multi-trait prediction framework using artificial intelligence, leveraging 2700 parent combinations and their offspring field performance data from the Sugarcane Research Institute of Guangxi Academy of Agricultural Sciences. Five machine learning paradigms were selected based on data characteristics: tree-based models (GBDT, XGBoost) for structured tabular data and nonlinear trait interactions; attention-based tabular models (TabTransformer, TabNet) for subtle cross-trait dependencies; and an MLP as a baseline. All models were optimized via 80/20 stratified train–test split, class-weighted loss, and cross-validated grid search. GBDT achieved the best overall performance with a macro F 1 score of 0.7316, Hamming loss of 0.2052, and sample accuracy of 0.5630, excelling in predicting sucrose content, cane yield, and smut resistance. XGBoost performed comparably, while TabTransformer offered complementary advantages with a higher F 1 score (0.6829) on overall agronomic performance. These results indicate the potential of using artificial intelligence (AI), particularly machine learning (ML), to increase the predictive power and robustness through integrated AI approaches in the future. This phenotype-based framework shows the value of ML as an efficient decision support tool that can help breeders prioritize cross combinations and optimize resource use, thereby reducing reliance on extensive field trials. While the potential of AI in accelerating variety development is evident, its routine application in real-world commercial breeding requires validation.

The biphasic regulatory effect of adenosine A2B receptor in ischemic brain injury and its therapeutic potential - Xu Rui; Wang Xi; Li Mengzhu; Su Peiwei; Liu Mudong; Zhu Chao; Luo Wanyu; Zhao Haijun (Purinergic Signalling, 2026)

High breeding potential for growth exists in normal, black, and golden shell lines of tetraploid Fujian oyster revealed through three generations of mass selection - Yuanxin Liang; Qi Li; Xianchao Bai; Geng Cheng; Jianmin Zhou; Rui Xu; Fanzhi Chu; Zhiyang Cui; Chengxun Xu; Wenshu Luo (Aquaculture, 2026)

Microbiome differentiation and phenotypic variation of Pyropia haitanensis under two contrasting aquaculture environments - Fengjuan Li; Yi Liu; Qijun Luo; Juanjuan Chen; Rui Yang; Wenrong Zhu; Huifeng Cai; Haimin Chen (Aquaculture, 2026)

Faecalibacterium prausnitzii derived postbiotic attenuates PEDV-induced mitochondrial apoptosis through blocking viral entry - Lingcong Deng; Rui Luo; Shihan Yang; Letian Li; Nan Li; Yu Dong; Jiayi Hao; Ju Li; Anqi Deng; Xueyan Ai; Maopeng Wang; Chang Li (Veterinary Microbiology, 2026)

Quantifying the nonlinear interactions of 2D/3D building and green space morphology on land surface temperature across different urban functional zones - Haiyan Luo; Rui Zhou; Chunlin Li; Qun Ma; Xuening Fang; Yina Hu; Xinlin Lv; Zining Dong; Yujing Tian; Shubo Fang (Sustainable Cities and Society, 2026)

Mechanistic insights into soil compaction tolerance in sugarcane: Jasmonate signaling and root structural adaptation underpin compaction resilience - Xiaoyan Liu; Ting Luo; Rui Yan; Yijie Li; Qiang Liang; Ling Yao; Weizan Wang; Prakash Lakshmanan (Soil and Tillage Research, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

Synergistic recovering Fe, Al and biochar through biomass-reduction alkali roasting and wet magnetic separation for red mud (RM): behavior and mechanism - Rui Xu; Cunfang Lu; Min Zhang; Cheng Tian; Dan Luo; Lin Yang; Wenlin Xie; Zhengnan Zhong; Juan Wen (Minerals Engineering, 2026)

Enhancement of hydrocyclone separation for fine-grained bauxite based on interface control - Geng Luo; Bingjun Wang; Rui Wang; Qiuhan Shi; Xiaokang Yan; Haijun Zhang; Lijun Wang (Minerals Engineering, 2026)

Topographic roughness of continuous ejecta deposits of kilometer-size simple craters on the Moon and Mars - Hanxing Ouyang; Zhiyong Xiao; Yichen Wang; Yizhen Ma; Fanglu Luo; Rui Xu (Geomorphology, 2026)

New insights into late Quaternary dust activity and its drivers on the Tibetan Plateau from loess records - Li Liu; Shengli Yang; Yuanlong Luo; Pushuang Li; Xiuyun Yang; Xin Wang; Jingzhao Zhang; Weiming Liu; Rui Li; Xiaomin Fang (Global and Planetary Change, 2026)

Deciphering the geological significance of carbonate clumped-isotope-based temperature during the Permian-Triassic transition in South China - Biao Chang; Zhaoyu Zeng; Xiaofeng Cheng; Weihao Zhang; Zhen Xu; Tianhu Pu; Chaojin Lu; William F. Defliese; Rui Wang; Xu Dai; Haijun Song; Genming Luo (Geochimica et Cosmochimica Acta, 2026)

Drying methods impact bioactive compounds in Siraitia grosvenorii fruit: Metabolomic insights - Li Li; Lihong Xie; Ping Yi; Ting Gan; Zhenmei Fan; Min Huang; Shiqi Wang; Dan Luo; Rui Pang; Fenglai Lu; Jinfeng Sheng; Jian Sun; et al. (Food Chemistry, 2026)

Rapid-gelating starch from potential ginger processing waste: Multi-scale structural analysis enabling high-precision 3D printing for health-focused food applications - Rui He; Shanshan Li; Jing Wang; Zhu Zhu; Wenhao Luo; Kun Pan; Fengwei Xie; Ying Chen; Tao Yang (Food Hydrocolloids, 2026)

Advancing screening of aquatic persistent, mobile, and toxic substances via integration of graph convolutional networks and multitask learning - Yang Chen; Rui Qiu; Jin Yin; Jingquan Wang; Peng Chen; Liping Luo; Hongguang Guo (Environmental Research, 2026)

Interfacial environment modulation by nanoneedle-shaped polyaniline for enhanced hydrogen isotope separation by water electrolysis - Rui Li; Guoyu Li; Penghui Xiong; Yuhan Wu; Ruidong Liu; Hang Zhong; Yue Yao; Xin Xiang; Wenhua Luo; Jingsong Xu (Chemical Engineering Journal, 2026)

A New Species of Diaporthe Section Betulicola (Diaporthomycetidae, Diaporthales) From China - Yi Lan Jin; Xing Yu Luo; Kamran Habib; Yu Lin Ren; Qing Yang; Li Li Liu; Chanhom Loinheuang; Yang Chen; Qi Rui Li (New Zealand Journal of Botany, 2026)
A new species in Diaporthaceae, Diaporthe fengtaiensis sp. nov., is described and illustrated from Southwestern China. A comparative morpho‐anatomical study and multilocus phylogenetic analysis (ITS, CAL , HIS , TEF1‐α , TUB2 ) confirmed its position within the section Betulicola of the genus Diaporthe . The taxon is characterized by immersed ascomata (270–420 × 290–410 µm), relatively large asci (70–115 × 9.5–13.5 µm), and 1‐septate, fusiform ascospores (18.5–25.6 × 4.5–6.5 µm). Its positioning in a separate branch in the phylogenetic tree makes it distinct from the other known species of the section. A complete taxonomic treatment, based on two collected specimens, is provided along with molecular phylogenetic analyses.

Automatic first-arrival picking based on clustering selection - Lei Gao; Xin-rui Luo; Yu Fang; Mei Yan (Applied Geophysics, 2026)

Mechanism of baicalein from Wudang Mountain Scutellaria baicalensis Georgi. against atopic dermatitis based on network pharmacology, transcriptomics and in vitro experimental validation - Liu Tang; Gang Liu; Dan Li; Tianshuai Wang; Chun Wang; Guangwen Luo; Rui Peng; Xu Cai (Natural Product Research, 2026)

WTAP-mediated m6A modification of PRMT1 regulates cuproptosis to promote anaplastic thyroid carcinoma progression - Guoli Feng; Changju Chen; Yi Luo; Rui Chen; Xinghong Tang; Taolang Li (Tissue and Cell, 2026)

tRNAGlu−CTC-1-1-derived small RNAs inhibit the proliferation of immature porcine Sertoli cells - Guo Ming; Cha Ding-rui; Yang Jin; Luo Jun; Zeng Wen-xian; Chen Xiao-xu (Theriogenology, 2026)

Zinc finger protein ZNF638 in brown fat deteriorates type 1 diabetes via retinol binding protein 4 - Meiyao Meng; Shuang Liu; Yinzhao Zhong; Jingyi Hu; Lijun Zhu; Jin Qiu; Rui Wang; Yuan Luo; Yingwen Wang; Wenhao Zhou; Guangyu Shan; Zhenyu Du; et al. (Science Bulletin, 2026)

Earthworm pretreatment enhances anaerobic biogas production through time-dependent structural modification of coal - Yunxia Niu; Daping Xia; Xiao Zhou; Bin Xu; Huizhen Chang; Kuo Jian; Rui Luo; Zhijia Yu; Haijiao Fu (Journal of Environmental Chemical Engineering, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Quantifying the impact of vegetation greenness change on surface urban heat islands across 133 major cities of China - Rui Yao; Zhihao Zhang; Wenjie Li; Hao Li; Shiya Zhu; Hongji Zhu; Chuan Wang; Dewei Luo; Ying Yang; Junli Li; Weitao Han; Xin Huang (Environmental Research, 2026)

Cadmium adsorption-desorption synergy drives spatial heterogeneity of grain cadmium enrichment in a subtropical limestone paddy region - Xinliang Liu; Shufang Pan; Rui Liu; Lei Luo; Ziqian Zhong; Qihong Zhu; Xionghui Ji; Daoyou Huang (Environmental Pollution, 2026)

Experimental investigation and analysis of monotonic and cyclic behaviour of a natural sand in intact and reconstituted states - Xiaotong Yang; Wenming Peng; Jian-Min Zhang; Jian Li; Qixun Luo; Fulong Ma; Rui Wang (Engineering Geology, 2026)

Biomimetic hydrogel delivers engineered exosomes loaded with DFO to regulate ferroptosis and chondrocyte metabolism for osteoarthritis amelioration - Bohan Li; Jingming He; Zhongyang Li; Yuexing Zhang; Youfeng Shen; Xueyuan Yi; Rui Luo (Chemical Engineering Journal, 2026)

Integrating graphic building group height distribution grids to assess city’s microclimate with wind-direction-dependent deep transfer learning neural networks - Qi Li; Wei Wang; Rui Ma; Jiayu Chen; Xiaowei Luo (Building and Environment, 2026)

Increased allochthonous dissolved organic carbon provides a competitive advantage for planktonic over benthic primary producers in shallow lakes - Heding Huang; Dong Luo; Rui Zhou; Pengfei Liu; Lei Li (Hydrobiologia, 2026)

Research progress on triterpenoids in the genus Rubus : a comprehensive review - Xi-Ya Li; Ting-Cai Dong; Yong-Fan Zi; Yan Luo; Yuan Li; Rui-Feng Mei; Le Cai (Natural Product Research, 2026)

Effect of environmental factors on the control of milky disease in Chinese mitten crab (Eriocheir sinensis) - Rui Zhang; Zhigang Zhao; Kun Guo; Xu Zhao; Xiangyi Deng; Shihui Wang; Liang Luo (Aquaculture, 2026)

Strengthening of MFC sensor performance by biomass materials: Characteristics and associated biological mechanisms - Rui Gan; Yingjie Zhou; Jia Chen; Hongbing Luo; Ke Zhang (Process Safety and Environmental Protection, 2026)

Finite-time rendezvous of heterogeneous cluster AUVs under intermittent communication and disturbances: A distributed adaptive hybrid observer-controller design - Bo Chen; Zhinan Peng; Rui Luo; Kaibo Shi (Ocean Engineering, 2026)

Corrigendum to “Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides” [Food Chem. 496(Part 2) (2025) 146787] - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2026)

Molecular characterization, transcriptional profiling, and immune functional analysis of CD94 from Nile tilapia (Oreochromis niloticus) - Yijian Huang; Guoling Luo; Dandan Wu; Zhongxin Hu; Jia Cai; Bei Wang; Yishan Lu; Zhiwen Wang; Rui Song; Jichang Jian; Yu Huang (Fish & Shellfish Immunology, 2026)

Synergistic surface plasmon resonance effect of Ag and S-scheme heterojunction in Ag/AgBr/Bi24O31Cl10 towards enhanced enrofloxacin removal: Performance, degradation pathways and synergistic mechanism - Xiao-Ju Wen; Qian Zhan; Hongyu Ye; Jing Xu; Binbin Qian; Rui Luo; Xiankun Wu; Zongtang Liu; Zhenghao Fei; Hai Guo (Environmental Research, 2026)

Single-atom Fe engineered-PANI/AC/MXene composite flow electrode for sustainable water desalination and electroplating wastewater treatment - Rui Chen; Yuzhan Luo; Hui Wang; Youyu Tian; Zhiqun Xie; Hui Wang; Zhiwei Jiang; Anqi Wang; Kai Yan; Zongsu Wei (Chemical Engineering Journal, 2026)

Effect of Mg(OH)2 addition on NH4H2PO4 powder in suppressing the explosion of volatile mixtures of methane and coal - Qiuhong Wang; Rui Guo; Jun Deng; Zhenmin Luo; Chi-Min Shu; Zezhou Song; Qingfeng Wang; Junjie Wu; Di Wu; Ran Liu (Chemical Engineering Journal, 2026)

Synergistic 3d-5d orbital interactions on oxygen vacancy-rich Pt/TiO2 for enhanced photothermal catalytic oxidation of propylene - Xiaoxiao Zhu; Weidong Yuan; Siyi Song; Tong Chen; Wenjun Xiong; Sibo Wang; Jinpeng Hu; Rui Liu; Zhu Luo; Jinlong Wang; Ang Gao; Yanbing Guo (Chemical Engineering Journal, 2026)

Influence of coal dust on flame propagation characteristics and spectral features of gas explosion - Qiuhong Wang; Zezhou Song; Jun Deng; Zhenmin Luo; Wei Gao; Yating Zhang; Guoqiang Dong; Rui Guo; Di Wu (Chemical Engineering Journal, 2026)

Depth-dependent effects of vegetation restoration on soil quality in ion-adsorbed rare earth leach residues: Insights from soil functions - Heng Zhang; Xianzhen Luo; Rui Zhang; Li Zhou; Rufeng Guo; Yuanwen Kuang; Dazhi Wen; Biao Qiu; Lingling Zhang (CATENA, 2026)

Avicularin induces apoptosis in NSCLC by promoting USP7-mediated degradation of FOXM1 - Jiangyue Du; Kuai Yu; Jian Zeng; Lijuan Ma; Tingting Yu; Rui Yu; Taobo Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Soluble TREM1 Contributes to Aging-Related Neurodegeneration via ROBO2/ERK Pathway - Jing-Wen Qi; Xin-Yu He; Yu-Cheng Gu; Zi-Jian Luo; Rui Duan; Ying-Dong Zhang; Yi Xie; Teng Jiang (Molecular Neurobiology, 2026)

Mechanisms of Action of FUNDC1 in Cerebral Ischemia-Reperfusion Injury - Xin-Yi Zou; Luo-Yang Cai; Jin Zhang; Ying Yuan; Jie Song; Zhao-Duan Hu; Rui Peng; Xiao-Feng Ruan; Xiao-Ming Zhang (Molecular Neurobiology, 2026)

Xinshuaining preparation ameliorates doxorubicin-induced cardiac injury in heart failure rats by regulating gut microbiota - Qian Nie; Jue Zhao; Sattar Haseeb; Siwei Deng; Xin Zhang; Rui Wang; Xu Luo; Wen Xie (Drug Delivery and Translational Research, 2026)

A near-infrared hemicyanine-derived fluorescent probe for sulfite detection in biomedical investigate - Kai Wang; Dan-Xian Cai; Hao-Xiang Jiang; Zi-Rui Luo; Hong-Rui Zhan (Analytica Chimica Acta, 2026)

Ligation-mediated circuit-driven cascade amplification with high utilization rate of template for lncRNA MALAT1 detection in cancer mice tissues - Yuyan Huang; Fan Huang; Qianqian Du; Rui Yu; Jingfeng Lan; Junwei Luo; Hongli Chen; Huige Zhang (Analytica Chimica Acta, 2026)